The problem of developing e-payment systems in Algeria as an entry point for e-commerce - bouziane, fatiha; selmani, hanna (Journal of Research in Finance and Accounting, 2025)
This study aims to try to shed light on the reality of e-payment systems in Algeria and the efforts exerted to develop it as the basic structure for the development of electronic commerce by analyzing the various numbers and indicators available around it. We used the descriptive analytical method for that. The study concluded that Algeria has made great strides in the development of electronic payment systems, but this development remains late and weak compared to the capabilities available at the level of Algeria and also compared to the development taking place at the international level.